L'intervention du juge dans la vie de la société en droit français et en droit OHADA - Mugisho Kazingufu, Jean-Jacques (Université de Goma, 2017)
Keywords: Corporate law; Droit des sociétés; Intérêt social; Règlement de conflits

Les enjeux de la déjudiciarisation - Cimamonti, Sylvie; Perrier, Jean-Baptiste (Mission de recherche Droit et Justice, 2017)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration (Publications of the Masaryk University, theoretical series, editions Scientia, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

Réflexion sur la notion et le régime de la médiation au sein des modes amiables de résolution des différends : à partir des expériences de médiation dans les ressorts des Cours d’appel d’Aquitaine (Agen/Bordeaux/Pau), de Paris et de Lyon - Larribau-Terneyre, Virginie; Lecourt, Arnaud; Brus, Florence; Alvarez Elorza, Alexis; Drouiller, Camille; Sane, Claude MIchel (Mission de recherche Droit et Justice, 2017)